2010
DOI: 10.1007/s10549-010-1072-z
|View full text |Cite
|
Sign up to set email alerts
|

Isolated and combined action of tamoxifen and metformin in wild-type, tamoxifen-resistant, and estrogen-deprived MCF-7 cells

Abstract: Resistance to tamoxifen (TAM) and aromatase inhibitors represents a major drawback to the treatment of hormone-dependent breast cancer, and strategies to overcome this problem are urgently needed. The anti-diabetic biguanide metformin (MF) exerts pleiotropic effects which could enhance the effectiveness of available hormonal therapies. This study modeled several aspects of hormonal therapy in women and examined the effectiveness of MF under those conditions. For cell growth evaluation, wild-type (wt), TAM-resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 60 publications
4
25
0
4
Order By: Relevance
“…In primary human breast adipose stromal cells, metformin treatment led to an increase in the phosphorylation of AMPK, which was associated with an inhibition of nuclear translocation of CRTC2, a CREB co-activator known to increase aromatase expression (Brown et al 2010). Furthermore, metformin interacted additively with tamoxifen to reduce breast cancer cell proliferation (Berstein et al 2010b). These results indicate that metformin may represent a potentially effective therapy in women with ER-positive breast tumours.…”
Section: In Vitro Models Of Anti-cancer Effects Of Metforminmentioning
confidence: 83%
“…In primary human breast adipose stromal cells, metformin treatment led to an increase in the phosphorylation of AMPK, which was associated with an inhibition of nuclear translocation of CRTC2, a CREB co-activator known to increase aromatase expression (Brown et al 2010). Furthermore, metformin interacted additively with tamoxifen to reduce breast cancer cell proliferation (Berstein et al 2010b). These results indicate that metformin may represent a potentially effective therapy in women with ER-positive breast tumours.…”
Section: In Vitro Models Of Anti-cancer Effects Of Metforminmentioning
confidence: 83%
“…The main downstream effect of AMPK activation is the inhibition of mTOR [26]. Recent study showed that the effect of p-S6K1 (a target of mTOR) inhibition by metformin is stronger in tamoxifen-resistant MCF-7 cells than in wild-type MCF-7 cells and the additive effect of metformin combined with tamoxifen is also greater in tamoxifen-resistant MCF-7 cells [27]. In addition, the mTOR inhibition by rapamycin derivatives may activate compensatory pathways such as insulin-like growth factor-1 receptor (IGF-1R)/PI3 K signaling to Akt [28], and this collateral effect of mTOR blockade is another potential explanation for the limited activity of mTOR inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…Given that aromatase inhibitors are now the mainstay of neoadjuvant, adjuvant, and extended treatment in postmenopausal women with breast cancer, the potential for synergism between an aromatase inhibitor and metformin is under exploration in a Korean neoadjuvant trial and is planned for an international extended adjuvant trial. For premenopausal women, where tamoxifen remains the principal adjuvant therapy for ER-positive breast cancer, the additive effects of metformin to tamoxifen, at least in terms of reducing cell proliferation (46), merits subgroup analysis within the ongoing MA32 adjuvant metformin trial (47).…”
Section: Metforminmentioning
confidence: 99%